2019
DOI: 10.1186/s12886-019-1171-5
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of visual acuity and retinal morphology following resolved chronic central serous chorioretinopathy

Abstract: Purpose Central serous chorioretinopathy (CSCR) is a complex ocular entity that, in its chronic form, can lead to serious visual impairment and morphological damage to the retina. The aim of the current retrospective study was to evaluate the damage present after long-standing but resolved central serous chorioretinopathy and refer it to healthy individuals. Correlations between measurable factors—for example, duration of the disease, baseline retinal morphological parameters, or pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 52 publications
3
24
0
1
Order By: Relevance
“…As the pathogenesis and pathophysiology of CSC have not been fully explained, the available treatment modalities are suboptimal, especially in long-standing cases [ 2 , 6 ]. Growing evidence indicates that the pathomechanism of CSC is associated with dysfunction of the thickened choroid (an important risk factor), with subsequent impairment of the RPE [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the pathogenesis and pathophysiology of CSC have not been fully explained, the available treatment modalities are suboptimal, especially in long-standing cases [ 2 , 6 ]. Growing evidence indicates that the pathomechanism of CSC is associated with dysfunction of the thickened choroid (an important risk factor), with subsequent impairment of the RPE [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first retrospective study to quantitatively investigate the vessel density ratio of the superficial choroidal layer at the leakage point of patients with acute CSC using OCTA. A previous study by Chan et al (14,28) has shown that the high signal intensity of the choriocapillaris on OCTA is more common in chronic CSC. However, according to our data, a reduced blood signal intensity in the superficial choriocapillaris layer of OCTA occurs more frequently in acute CSC eyes, which corresponds to the location of the leakage point on FFA, and most of them are not surrounded by high signals, as described in chronic CSC eyes.…”
Section: Discussionmentioning
confidence: 89%
“…We can aggregate the nature of the episode as an alternative and complementary way to classify the CSC spectrum. With effect from first recognition and during long-term follow-up, controlling biomarkers could help to define the case management recommendation [42][43][44][45][46][47][48].…”
Section: Complementary Analysismentioning
confidence: 99%
“…Autofluorescence and infrared autofluorescence evidence, such as persistence of hyperautofluorescence of the serous detachment zone, a granular pattern sometimes associated with the appearance of descending tracks, could be associated with long evolution or a recurrent situation [42][43][44][45][46][47][48][49][50][51][52][53]. IVFA in acute CSC typically shows two patterns: inkblot or smoke stack.…”
Section: Complementary Analysismentioning
confidence: 99%
See 1 more Smart Citation